EMPOWERMENT OF TRADITIONAL SPORTS IN LOWER GRADE ELEMENTARY SCHOOLS IN BANJAR REGENCY - Firdaus, Muhammad; Mashunah, Dorrah; Ghani, Muhammad Ilham; Harmono, Zelicha Lutfiah; Oktavia, Ramanda; Kahri, Ma'ruful; Ichsan, Daeng Arifmul; Anggara, Norma; Warni, Herita (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
This article describes a national culture that is spread throughout the country and is slowly disappearing and is difficult to find in schools. This occurs as a result of developments in increasingly modern times, so that students are slowly switching from traditional games to modern games in the form of online games. This research was carried out at the Tambak Sirang Baru State Elementary School, Banjar Regency, South Kalimantan. The aim of this research is to introduce and socialize traditional games, especially Gobak Sodor.The research method is a quantitative experimental approach type one group pretest-posttest with a sample consisting of 10 grade 1 students. The research instrument is a questionnaire using the Guttman scale to measure participants' knowledge of traditional games before and after socialization. The research results showed that participants' understanding and interest in traditional games increased after socialization. Data analysis using percentages showed that the majority of participants had low knowledge (40-55%) 3 students or very low (0-40%) 5 students recognized traditional games before socialization. The improvement seen after socialization, most participants obtained a very high level of knowledge (85-100%) 5 students out of 10 students and very low (0-40%) none. Therefore, it is hoped that activities supporting traditional games such as Gobak Sodor can be a solution to revitalize children's interest and understanding of Indonesia's cultural heritage. This article states that in the context of PJOK learning, traditional games not only teach physical aspects but also build values, culture and cooperative strategies in group activities. From the results of this research, it is hoped that traditional games will become an effective educational tool for developing the physical, social and skill aspects of modern children.